2023
DOI: 10.1186/s12951-023-01931-1
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dots induce pathological damage to the intestine via causing intestinal flora dysbiosis and intestinal inflammation

Abstract: Background Carbon dots (CDs), as excellent antibacterial nanomaterials, have gained great attention in treating infection-induced diseases such as periodontitis and stomatitis. Given the eventual exposure of CDs to the intestine, elucidating the effect of CDs on intestinal health is required for the safety evaluation of CDs. Results Herein, CDs extracted from ε-poly-l-lysine (PL) were chosen to explore the modulation effect of CDs on probiotic beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…However, other researchers found out that CDs may have potential safety risks. For example, Jia et al demonstrated that positively charged PL-CDs have the possibility of resulting in intestinal flora dysbiosis via inhibiting probiotic growth and simultaneously activating intestinal inflammation (Jia et al, 2023). They are verified to limit the activity of intestinal epithelial cells in vitro and could result in damage to the intestines.…”
Section: Clinical Translation and Limitationsmentioning
confidence: 99%
“…However, other researchers found out that CDs may have potential safety risks. For example, Jia et al demonstrated that positively charged PL-CDs have the possibility of resulting in intestinal flora dysbiosis via inhibiting probiotic growth and simultaneously activating intestinal inflammation (Jia et al, 2023). They are verified to limit the activity of intestinal epithelial cells in vitro and could result in damage to the intestines.…”
Section: Clinical Translation and Limitationsmentioning
confidence: 99%